Fiberglass Shipbuilding Training for Fishermen in Aceh Singkil : Pelatihan Pembuatan Kapal Fiberglass Untuk Nelayan di Aceh Singkil - Muchlis, Yusrizal; Rahmawati, Cut; Amin, Amri; Lindawati, Lindawati; Zardi, Muhammad; Meliyana, Meliyana (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
The construction of fishing boats in Aceh Singkil Regency continues to rely on wood as the primary material. This practice poses challenges for fishermen in expanding their fishing production capacity, as procuring sufficient wood for larger boats becomes a significant hurdle. The Aceh Singkil Regency government has imposed restrictions on forest logging for industrial purposes. In response to this limitation, the community service team from Abulyatama University has proposed an alternative solution—exploring materials other than wood that can offer greater boat capacity. The implementation of this initiative involves hands-on training for fishermen and the evaluation of product quality. The step-by-step processes undertaken by fishing groups in boat construction include: (1) interpreting design drawings, (2) crafting molds, (3) applying gelcoat, (4) constructing boat bodies, (5) creating coolboxes, (6) finishing, and (7) conducting sea trials for the fishing boats. The tangible outcome of this endeavor is a fully functional product crafted by the fishing group. The community exhibited remarkable enthusiasm throughout the process, as the fishing group actively participated in every stage of boat construction. This training proved highly beneficial for the fishermen, who strongly desire continued guidance in future shipbuilding endeavors. Certificates were awarded to the fishermen upon completing the activity as a commendation for their commitment to the training process.